2022
DOI: 10.1093/sleep/zsac061
|View full text |Cite
|
Sign up to set email alerts
|

Estimating circadian phase in elementary school children: leveraging advances in physiologically informed models of circadian entrainment and wearable devices

Abstract: Study Objectives Examine the ability of a physiologically based mathematical model of human circadian rhythms to predict circadian phase, as measured by salivary dim light melatonin onset (DLMO), in children compared to other proxy measurements of circadian phase (bedtime, sleep midpoint, and waketime). Methods As part of an ongoing clinical trial, a sample of 29 elementary school children (mean age: 7.4 +/- .97 years) comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…However, light exposure in this study was measured from a wrist-worn device (ActiGraph GT3X+), which may not accurately capture light at the eye level. The GT3X device also has a red casing 13 , which may reduce its light measurement sensitivity 42 . Location and exact date data of measurement were not available, so the influence of location and specific time of year on the results was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, light exposure in this study was measured from a wrist-worn device (ActiGraph GT3X+), which may not accurately capture light at the eye level. The GT3X device also has a red casing 13 , which may reduce its light measurement sensitivity 42 . Location and exact date data of measurement were not available, so the influence of location and specific time of year on the results was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The Hannay Model simulations were conducted using an explicit Runge–Kutta method of order 5 (4) numerical integration written in Python (https://github.com/khannay/Circadian-DLMO-Prediction). Because the Hannay Model was previously validated to predict dim‐light melatonin onset among children using activity [32], activity data were used to compute the ESRI. Prior research has also indicated that, when using wrist‐worn devices, activity data provide a more robust estimate of input to the circadian signal than light data [39, 40], likely because of various limitations of measuring light from the wrist (e.g., obstruction by apparel, a light sensor from the wrist may not correspond to retinal light input, accelerometer performance is typically more stable than light sensors).…”
Section: Methodsmentioning
confidence: 99%
“…As with other models, estimates of circadian phase are based on inputs to the clock such as light exposure or activity as measured by a wearable wrist‐worn device [31]. Using children's activity patterns, the Hannay Model was shown to predict children's circadian phase as assessed by dim‐light melatonin onset with a mean absolute error of 31 minutes among a sample of 29 children aged 5 to 8 years [32]. The Hannay Model also has been used to accurately predict circadian phase in shift workers [33].…”
Section: Introductionmentioning
confidence: 99%
“…Using the Sadeh algorithm [ 62 ] epochs will be scored as sleep or wake. According to established protocols [ 17 , 63 ], each sleep episode reported in the parent diary will be inspected in the activity data. Nights will be considered valid if the participant provided 20 minutes of wear time before sleep onset.…”
Section: Methodsmentioning
confidence: 99%